Older adults and healthcare professionals have limited awareness of the link between the Mediterranean diet and the gut microbiome for healthy aging - O’Mahony, Lauren; O’Shea, Emma; O’Connor, Eibhlís M.; Tierney, Audrey; Harkin, Mary; Harrington, Janas; Kennelly, Sharon; Arendt, Elke; O’Toole, Paul W.; Timmons, Suzanne (Frontiers in Nutrition, 2023)
Objectives: Strategies to improve the gut microbiome through consuming an improved diet, including adopting the Mediterranean Diet (MD), may promote healthy ageing. We explored older adults’ and healthcare professionals’ (HCPs) perspectives of the MD, gut health, and microbiome for their role in healthy ageing. Design: Phenomenological qualitative Setting: Community-dwelling older adults and HCPs in primary and secondary care in Ireland. Participants: Older adults (aged 55+ years), recruited through social, retirement and disease-support groups. HCPs recruited through researcher networks and professional associations. Measurements: Semi-structured 1:1 interviews and focus groups (FGs) conducted remotely with older adults and HCPs separately. Interviews/FGs were recorded, transcribed, and coded using inductive thematic analysis. Results: Forty-seven older adults were recruited (50% male; 49% aged 60-69 years; 28% 70+), and 26 HCPs including dietitians (n=8); geriatricians (n=6); clinical therapists (n=4); nurses, pharmacists, catering managers, and meal-delivery service coordinators (n=2 each). Older adults considered the MD “a nice way to enjoy food”, good for cardiovascular health and longevity, but with accessibility and acceptability challenges (increased salads/fish, different food environments, socio-cultural differences). HCPs felt the MD is included in healthy eating advice, but not overtly, mostly through the promotion of mixed-fibre intake. Older adults considered ‘live’ yoghurt and probiotics, and to a lesser extent fibre, to maintain a ‘healthy gut’, suggesting the gut has “something to do with” cognitive and digestive health. Overall, microbiota-health effects were considered “not common knowledge” among most older adults, but becoming more topical among both professionals and the public with advancing scientific communication. Conclusions: While ‘gut health’ was considered important, specific effects of the MD on gut microbiota, and the significance of this for healthy ageing, was under-recognised. Future efforts should explain the importance to older adults of maintaining the gut microbiota through diet, while appreciating perspectives of probiotic products and supplements.